2009
DOI: 10.1007/s00405-009-0922-y
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and treatment results of laryngopharyngeal reflux in chronic obstructive pulmonary disease

Abstract: Laryngopharyngeal reflux (LPR) is defined as the movement of gastric content towards the larynx and the pharynx and it may cause respiratory symptoms or difficulty in their control. We aimed to find the frequency of LPR in chronic obstructive pulmonary disease (COPD) patients and to investigate its effect on COPD symptoms and the results of its treatment. At baseline 30 (20 male, 10 female, mean age: 65 +/- 10 years) COPD patients completed LPR and COPD symptom questionnaires and 13 (44%) were diagnosed with L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 20 publications
0
37
1
1
Order By: Relevance
“…Of the 11 articles, 7 met the inclusion criteria and were included in the analysis (Figure 1). ( 4 , 19 , 44 - 48 ) The characteristics of the studies included in the meta-analysis are presented in Table 1. No unpublished or ongoing studies were included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 11 articles, 7 met the inclusion criteria and were included in the analysis (Figure 1). ( 4 , 19 , 44 - 48 ) The characteristics of the studies included in the meta-analysis are presented in Table 1. No unpublished or ongoing studies were included.…”
Section: Resultsmentioning
confidence: 99%
“…The major issues about the effect of GER in COPD exacerbations are how exacerbations are determined or defined and whether such determinations are carried out prospectively or retrospectively. Recent retrospective studies ( 47 , 48 ) suggested that GER symptoms were associated with exacerbations; however, in those studies, the subjects were asked to report the number of exacerbations that had occurred during the previous year, which was an approach that could result in a recall bias. To solve this type of problem, other studies ( 19 , 45 ) utilized a prospective questionnaire-based data collection system that allowed us to identify exacerbations according to a more reliable definition of COPD exacerbation, such as the modified criteria by Anthonisen et al ( 20 ) The prospective analyses of Terada et al ( 19 ) and Hurst et al ( 4 ) presented the most reliable information about exacerbations and were the most influential studies on the forest plots about the risk of COPD exacerbations associated with GER (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…GERD is a well-known comorbidity of COPD, 12,15 and is negatively associated with symptoms, quality of life, and exacerbation of COPD. [16][17][18] However, the association between …”
Section: Discussionmentioning
confidence: 99%
“…La place du traitement anti-reflux n'est pas clairement établie : certaines études n'ont retrouvé aucun bénéfice quant à l'utilisation d'un traitement par IPP ou d'un antagoniste des récepteurs H2 [50,51] tandis que d'autres ont montré une amélioration des symptômes respiratoires [52] et une diminution des exacerbations [53] après instauration d'un IPP chez des patients BPCO. Il est vraisemblable que, tout comme dans l'asthme, les patients atteints de BPCO ayant un reflux symptomatique doivent recevoir un traitement anti-reflux, ce qui participera à l'amélioration significative de leur qualité de vie [54].…”
Section: Bronchopneumopathie Chronique Obstructive Dilatation Des Brunclassified